Madrasah Principal Leadership Model and Implementation of the Al-Qur'an Memorization Program in Improving the Quality of Education at MIN 3 Sumenep Tanjung Saronggi Sumenep 2026 - Siswanto Siswanto; Musleh Wahid (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Improving the quality of education in Islamic elementary schools (madrasah ibtidaiyah) depends heavily on the principal's managerial skills in formulating flagship programs relevant to community needs. MIN 3 Sumenep integrates the Quranic memorization program not merely as an extracurricular activity, but as a strategic instrument for building the institution's brand and producing spiritually competitive graduates. One of MIN 3 Sumenep's flagship programs is the implementation of the Quranic memorization program, an effort to improve the quality of education at the school, located in Tanjung, Saronggi. This is based on the observation that MIN 3 Sumenep is a formal educational institution with a significant student population. This analysis aims to describe the contribution of the principal's leadership model to improving the quality of education through the Quranic memorization program and to explain the progress of its implementation. This research used qualitative methods with a descriptive approach. The research subjects consisted of the principal of MIN 3 Sumenep and the Quranic memorization teacher. The research object focused on the principal's leadership model and the implementation of the Quranic memorization program. Data were collected through observation, in-depth interviews, and documentation. The research results show that: (1) the madrasah principal's leadership model is democratic and participatory; (2) the development of the madrasah's vision, mission, objectives, and work plan is carried out through a deliberation mechanism that includes planning, organizing, and monitoring functions; (3) the applied Qur'an memorization methods include the tasmi' and murajaah techniques; and (4) the madrasah committee and parents provide significant support for the program's success.